What is Hidden in Västerbotten’s Stomach? On Augustine and Torgny Lindgren’s Minnen - Bak, Krzysztof (Journal of Northern Studies, 2014)
The article investigates the complex intertextual dialogue between Torgny Lindgren’s Minnen (2010) and Augustine’s Confessions, from which Lindgren has taken the motto of his autobiography. By using the patristic intertext as a starting point, the investigation intends to show how Lindgren has constructed his image of Västerbotten. The article is divided into four parts. The first part (I), establishes the heuristic principles of the investigation, which adhere to the recent tendency in patristic studies to observe the heterogeneous character of Augustine’s world of thought. The second part of the article (II) charts parallels between text and intertext in their portrayal of grace, evil, and man. It emerges that those elements of Lindgren’s world view which are particularly closely related to Augustinian theology are also the ones that possess a particularly strong Västerbottnian character. This intertextual affinity can be explained not only with reference to the Lutheran tradition of Västerbotten, but also has to be related to the text’s specific structure of memoria, which is unravelled in the remaining parts (III–IV). On the basis of modern cultural anthropological theories of memory, the third part demonstrates that most of the differences between text and intertext can be linked to the cultural memory of modernity, and document the rise and fall of industrial subjectivity. Lindgren embeds his autobiographical version of Västerbotten into the basic structure of modern memory, transforms it into a quasi-subject, and taints it with the symptoms of decay that plague the industrial ‘I.’ In the same as Western modernity, Minnen draws the majority of its metaphors of dissolution from Augustine’s paradigmatic doctrine of sin. The fourth part of the article (IV) aims to analyse the autobiography’s mechanisms of substitution. It is argued that these attempt—in analogy to many Western critics of modernity—to counteract the crisis of industrial cultural memory by reviving the Augustinian forms of memoria and creating a synthesis of pre-industrial and industrial. Within the quasi-subject of Västerbotten and its wealth of agrarian objects, Lindgren finds adequate metaphorical models for use in his compensatory project of counter-memory. The article concludes by observing that, just as Minnen’s productive dialogue with Augustine allows it to recapitulate the history of Western memory, Lindgren’s Västerbotten is elevated to the status of a universal symbol of European consciousness and its fate.